2003
DOI: 10.1136/ard.62.2.151
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarthritis of finger joints in Finns aged 30 or over: prevalence, determinants, and association with mortality

Abstract: Ann Rheum Dis 2003;62:151-158 Background: Prevalence and risk factors of osteoarthritis (OA) in finger joints have been amply explored in previous studies. However, no study has focused on finger joint OA as a predictor of mortality. Objective: To investigate finger joint OA for its associations with alleged risk factors and with life expectancy in an extensive health survey. Methods: From 1978 to 1980 a representative population sample of 8000 Finns aged 30 years or over was invited to participate in a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
123
1
5

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(140 citation statements)
references
References 49 publications
11
123
1
5
Order By: Relevance
“…When contrasting this study's findings with those of population-based surveys conducted in the Western populations, the prevalence of spine and shoulder OA was relatively higher [3,18,34,35], whereas the prevalence of hip and hand OA was lower [5,11,13,27,28,30,40] and that of knee OA was similar to or slightly higher than that of the Western populations (Table 3) [5,10,22,28]. In comparison with studies on other Asian populations, the prevalence of hip, knee, shoulder, and hand OA was similar [7,15,26,27,39,40], whereas the prevalence of spine OA was slightly lower than the reported prevalence [24].…”
Section: Discussioncontrasting
confidence: 38%
See 2 more Smart Citations
“…When contrasting this study's findings with those of population-based surveys conducted in the Western populations, the prevalence of spine and shoulder OA was relatively higher [3,18,34,35], whereas the prevalence of hip and hand OA was lower [5,11,13,27,28,30,40] and that of knee OA was similar to or slightly higher than that of the Western populations (Table 3) [5,10,22,28]. In comparison with studies on other Asian populations, the prevalence of hip, knee, shoulder, and hand OA was similar [7,15,26,27,39,40], whereas the prevalence of spine OA was slightly lower than the reported prevalence [24].…”
Section: Discussioncontrasting
confidence: 38%
“…On the other hand, we also found a higher prevalence of hand OA in females compared with males, and this sex discrepancy is a universal finding [11,40]. However, when detailed comparisons were made according to pattern of joint involvement and sex, these sex disparities showed more diverse changes.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Kalichman et al (2006) found a statistically significant association between radiographic hand OA and ischemic heart disease and gastrointestinal diseases. OA is also associated with a higher risk of mortality independent of age and comorbidities (Munger et al 1999;Haara et al 2003Haara et al , 2004.…”
Section: Biomarkers Of Agingmentioning
confidence: 99%
“…Rheumatoid arthritis (RA) is a chronic, progressive, and disabling autoimmune disease that is the second most common type of arthritis, affecting 0.8% of the UK adult population. Patients with OA or RA are at significantly higher risk of cardiovascular (CV) morbidity and mortality compared with the general population 2,3,4,5,6,7,8 . Hypercholesterolemia is one of the established CV risk factors with an increased prevalence among patients with OA or RA.…”
mentioning
confidence: 99%